Asymmetric temporal envelope encoding: Implications for within- and across-ear envelope comparison - Anderson, Sean R. (J Acoust Soc Am, 2019)
Separating sound sources in acoustic environments relies on making ongoing, highly accurate spectro-temporal comparisons. However, listeners with hearing impairment may have varying quality of temporal encoding within or across ears, which may limit the listeners' ability to make spectro-temporal comparisons between places-of-stimulation. In this study in normal hearing listeners, depth of amplitude modulation (AM) for sinusoidally amplitude modulated (SAM) tones was manipulated in an effort to reduce the coding of periodicity in the auditory nerve. The ability to judge differences in AM rates was studied for stimuli presented to different cochlear places-of-stimulation, within- or across-ears. It was hypothesized that if temporal encoding was poorer for one tone in a pair, then sensitivity to differences in AM rate of the pair would decrease. Results indicated that when the depth of AM was reduced from 50% to 20% for one SAM tone in a pair, sensitivity to differences in AM rate decreased. Sensitivity was greatest for AM rates near 90 Hz and depended upon the places-of-stimulation being compared. These results suggest that degraded temporal representations in the auditory nerve for one place-of-stimulation could lead to deficits comparing that temporal information with other places-of-stimulation.